vault backup: 2025-02-16 18:52:21
This commit is contained in:
parent
c2d96ec2e5
commit
763c9022ca
27
.obsidian/plugins/obsidian-git/data.json
vendored
27
.obsidian/plugins/obsidian-git/data.json
vendored
@ -0,0 +1,27 @@
|
|||||||
|
{
|
||||||
|
"commitMessage": "vault backup: {{date}}",
|
||||||
|
"autoCommitMessage": "vault backup: {{date}}",
|
||||||
|
"commitDateFormat": "YYYY-MM-DD HH:mm:ss",
|
||||||
|
"autoSaveInterval": 5,
|
||||||
|
"autoPushInterval": 0,
|
||||||
|
"autoPullInterval": 5,
|
||||||
|
"autoPullOnBoot": true,
|
||||||
|
"disablePush": false,
|
||||||
|
"pullBeforePush": true,
|
||||||
|
"disablePopups": false,
|
||||||
|
"listChangedFilesInMessageBody": false,
|
||||||
|
"showStatusBar": true,
|
||||||
|
"updateSubmodules": false,
|
||||||
|
"syncMethod": "merge",
|
||||||
|
"customMessageOnAutoBackup": false,
|
||||||
|
"autoBackupAfterFileChange": false,
|
||||||
|
"treeStructure": false,
|
||||||
|
"refreshSourceControl": true,
|
||||||
|
"basePath": "",
|
||||||
|
"differentIntervalCommitAndPush": false,
|
||||||
|
"changedFilesInStatusBar": false,
|
||||||
|
"showedMobileNotice": true,
|
||||||
|
"refreshSourceControlTimer": 7000,
|
||||||
|
"showBranchStatusBar": true,
|
||||||
|
"setLastSaveToLastCommit": false
|
||||||
|
}
|
@ -121,7 +121,7 @@ $$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
|||||||
> Apply the chain rule to $x^4$
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
If we treat the above as a function along the lines of $f(x) = (x)^4$, and $g(x) = x$, then the chain rule can be used like so:
|
If we treat the above as a function along the lines of $f(x) = (x)^4$, and $g(x) = x$, then the chain rule can be used like so:
|
||||||
$$ 4(x)^3 * x $$
|
$$ 4(x)^3 * (1) $$
|
||||||
# Trig Functions
|
# Trig Functions
|
||||||
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
||||||
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
||||||
@ -150,12 +150,20 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
- $\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one
|
- $\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one
|
||||||
- $\dfrac{d}{dx} y = \dfrac{dy}{dx} = y'$
|
- $\dfrac{d}{dx} y = \dfrac{dy}{dx} = y'$
|
||||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||||
|
|
||||||
|
Given these facts:
|
||||||
|
1. Let $y$ be some function of $x$
|
||||||
|
2. $\dfrac{d}{dx} x = 1$
|
||||||
|
3. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||||
|
What's the derivative of $y^2$?
|
||||||
|
$\dfrac{d}{dx} y^2 = 2(y)^1 *\dfrac{dy}{dx}$
|
||||||
|
|
||||||
# Examples
|
# Examples
|
||||||
|
|
||||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||||
|
|
||||||
2. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
4. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||||
3. $= 4x^\frac{1}{3} - x^{-6}$
|
5. $= 4x^\frac{1}{3} - x^{-6}$
|
||||||
4. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
6. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||||
5. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
7. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||||
6. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
8. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
Loading…
x
Reference in New Issue
Block a user